Drosophila insulin pathway mutants affect visual physiology and brain function besides growth, lipid, and carbohydrate metabolism. - Murillo-Maldonado, J.M.; Sánchez-Chávez, G.; Salgado, L.M.; Salceda, R.; Riesgo-Escovar, J.R. (Diabetes, 2011)
Type 2 diabetes is the most common form of diabetes worldwide. Some of its complications, such as retinopathy and neuropathy, are long-term and protracted, with an unclear etiology. Given this problem, genetic model systems, such as in flies where type 2 diabetes can be modeled and studied, offer distinct advantages.We used individual flies in experiments: control and mutant individuals with partial loss-of-function insulin pathway genes. We measured wing size and tested body weight for growth phenotypes, the latter by means of a microbalance. We studied total lipid and carbohydrate content, lipids by a reaction in single fly homogenates with vanillin-phosphoric acid, and carbohydrates with an anthrone-sulfuric acid reaction. Cholinesterase activity was measured using the Ellman method in head homogenates from pooled fly heads, and electroretinograms with glass capillary microelectrodes to assess performance of central brain activity and retinal function.Flies with partial loss-of-function of insulin pathway genes have significantly reduced body weight, higher total lipid content, and sometimes elevated carbohydrate levels. Brain function is impaired, as is retinal function, but no clear correlation can be drawn from nervous system function and metabolic state.These studies show that flies can be models of type 2 diabetes. They weigh less but have significant lipid gains (obese); some also have carbohydrate gains and compromised brain and retinal functions. This is significant because flies have an open circulatory system without microvasculature and can be studied without the complications of vascular defects.